A Coculture of Enterobacter and Comamonas Species Reduces Cadmium Accumulation in Rice - Xing Wang; Qing Xu; Kang Hu; Gejiao Wang; Kaixiang Shi (Molecular Plant-Microbe Interactions, 2023)
The accumulation of cadmium (Cd) in plants is strongly impacted by soil microbes, but its mechanism remains poorly understood. Here, we report the mechanism of reduced Cd accumulation in rice by coculture of Enterobacter and Comamonas species. In pot experiments, inoculation with the coculture decreased Cd content in rice grain and increased the amount of nonbioavailable Cd in Cd-spiked soils. Fluorescence in situ hybridization and scanning electron microscopy detection showed that the coculture colonized in the rhizosphere and rice root vascular tissue and intercellular space. Soil metagenomics data showed that the coculture increased the abundance of sulfate reduction and biofilm formation genes and related bacterial species. Moreover, the coculture increased the content of organic matter, available nitrogen, and potassium and increased the activities of arylsulfatase, β-galactosidase, phenoloxidase, arylamidase, urease, dehydrogenase, and peroxidase in soils. In subsequent rice transcriptomics assays, we found that the inoculation with coculture activated a hypersensitive response, defense-related induction, and mitogen-activated protein kinase signaling pathway in rice. Heterologous protein expression in yeast confirmed the function of four Cd-binding proteins (HIP28-1, HIP28-4, BCP2, and CID8), a Cd efflux protein (BCP1), and three Cd uptake proteins (COPT4, NRAM5, and HKT6) in rice. Succinic acid and phenylalanine were subsequently proved to inhibit rice divalent Cd [Cd(II)] uptake and activate Cd(II) efflux in rice roots. Thus, we propose a model that the coculture protects rice against Cd stress via Cd immobilization in soils and reducing Cd uptake in rice. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.